MENINGKATKAN INTERAKSI SOSIAL SISWA MELALUI LAYANAN BIMBINGAN KELOMPOK TEKNIK ROLE PLAYING PADA SISWA KELAS VIII SMP NEGERI 1 PERBAUNGAN T.A 2015/2016 - Rizky Yusrina Siregar (Jurnal Diversita, 2016)
The purpose of this study is to help improve students' social interaction through groupcounseling service engineering role playing in class VIII SMP Negeri 1 Perbaungan T.A2015/2016. This research uses research PTBK (Action Research Counseling) with twocycles, the first cycle and the second cycle consisting of planning, action, observation,reflection and evaluation. Data collection to encompass students who have low socialinteraction by using questionnaires of social interaction, in the form of an ordinal scalewith Likert scale form. The subject of this study is 6 students who have socialinteraction of students is low. Analysis of the data used in analysis techniquespercentage. The results showed an increase in the students' social interaction after theadministration of guidance services group role playing techniques. In the first cyclestudents' results increased social interaction by 50%. And the second cycle studentshasiln increased social interaction improved to 83.3%. From the results of the studyconcluded that the hypothesis can be accepted is by implementing role playing groupcounseling services can improve social interaction class VIII SMP Negeri 1 PerbaunganT.A 2015/2016.Keywords: Social Interaction Students, Guidance Group, Engineering Role Playing